Artificial neural network's prediction of wax deposition potential of Nigerian crude oil for pipeline safety - Obanijesu, Emmanuel; Omidiora, E. (Taylor & Francis Group, 2008)
Paraffin wax deposition from crude oil along pipeline is a global problem, making preventive methods preferred to removal methods. In this work, a neural network model based on mathematical modeling technique using regression analysis as the statistical tool was developed to predict the wax deposition potential of 11 reservoirs in Nigeria. Using the viscosity-pressure-temperature data obtained from these fields to supervise the model, the model accurately predicted the present real-life situation in each field. Conclusively, the model could be used to predict wax deposition potential of any reservoir that is yet to be explored provided the temperature used during prediction is close to the actual reservoir temperature.